Measurements of the moments of inertia of the Morane-Saulnier M.S.760 'PARIS' aircraft - Bradley, W. G. (College of Aeronautics, 1963)
This note describes the measurement of the moments of inertia, of a Morane-Saulnier M.S.760 'PARIS' aircraft. The moments of inertia in pitch, roll, and yaw were measured by the spring-constrained oscillation method. The cross-product of inertia and the inclination of the principal axis, were also determined by a variation of this method. Inertias were measured in three different fuel conditions. The results are given in Tables I - VI.